Cleaving paraoxon with hydroxylamine: Ammonium oxide isomer favors a Frontside attack mechanism - Lima, Marcelo F. [UNESP]; da Cruz, Priscilla Amanda Urbano; Fernandes, Maria Eduarda Camilo [UNESP]; Polaquini, Carlos [UNESP]; Miguel, Elizabeth L. M.; Pliego, Josefredo R.; Scorsin, Leandro; Oliveira, Bruno Surdi; Nome, Faruk (Wiley, 2019)
A detailed molecular understanding of the mechanisms of the dephosphorylation of phosphate triesters due to nucleophilic attack can be very useful for the design of nucleophiles that are more efficient. In this work, we report a combined experimental and theoretical study of the reaction of hydroxylamine with paraoxon. The profile of the reaction rate according to pH was determined, and it was found that protonated hydroxylamine was unreactive, while the neutral form reacted via the zwitterion tautomer, with an overall free energy barrier of 23.0 kcal mol -1 . The anionic form was the most reactive, with a free energy barrier of 18.1 kcal mol -1 . Computational calculations revealed 2 mechanisms for the nucleophilic attack of the zwitterion form: the usual backside attack and a new frontside attack mechanism. The former proceeded according to a 2-step associative mechanism, while the latter was a concerted single-step mechanism involving attack of the hydroxylamine oxygen on the phosphorus center and interaction of the NH 3 + group with the oxygen of the P═O group. The calculations indicated that the free energy barrier for the frontside attack was more favorable than the backside attack by 3 kcal mol -1 , supporting the notion that the observed reaction occurs by frontside attack. The reaction with the anionic hydroxylamine form occurred according to a single-step concerted A N D N mechanism.
Keywords: frontside attack; hydroxylamine; paraoxon; phosphoryl transfer